2015
DOI: 10.1210/en.2015-1206
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Cysteine Ligase Modifier Subunit (Gclm) Null Mice Have Increased Ovarian Oxidative Stress and Accelerated Age-Related Ovarian Failure

Abstract: Glutathione (GSH) is the one of the most abundant intracellular antioxidants. Mice lacking the modifier subunit of glutamate cysteine ligase (Gclm), the rate-limiting enzyme in GSH synthesis, have decreased GSH. Our prior work showed that GSH plays antiapoptotic roles in ovarian follicles. We hypothesized that Gclm(-/-) mice have accelerated ovarian aging due to ovarian oxidative stress. We found significantly decreased ovarian GSH concentrations and oxidized GSH/oxidized glutathione redox potential in Gclm(-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 86 publications
3
47
1
Order By: Relevance
“…In our study, we observed an up-regulation of Cox4 and Cox5a mRNA in the adipose tissue of O 3 -exposed mice. The proteins encoded by Gclm and Scd1 are rate-limiting enzymes in glutathione synthesis and fatty acid metabolism respectively, and are both important regulators in oxidative stress (Lim et al 2015; Liu et al 2011; Yang et al 2002). The expressions of Gclm and Scd1 both increased in visceral adipose tissue after exposure to O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed an up-regulation of Cox4 and Cox5a mRNA in the adipose tissue of O 3 -exposed mice. The proteins encoded by Gclm and Scd1 are rate-limiting enzymes in glutathione synthesis and fatty acid metabolism respectively, and are both important regulators in oxidative stress (Lim et al 2015; Liu et al 2011; Yang et al 2002). The expressions of Gclm and Scd1 both increased in visceral adipose tissue after exposure to O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS, however, leads to a state of oxidative stress and appears to be harmful to ovarian functions. In their study of mutated mice with a deficit of glutathione, the most abundant intracellular antioxidant, Lim et al described a faster decrease in the number of ovarian follicles in these mutated mice, related to an acceleration in primordial follicle depletion [101]. They also reported a higher percentage of small follicles with a heavy proliferation of granulosa cells, reflecting the accelerated recruitment of primordial follicles.…”
Section: Induction Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…CrVI also caused POF in F1 offspring by disrupting POF marker protein X-prolyl aminopeptidase-2 in a rat model (Banu et al, 2015). A recent study by Lim et al reports that increased ovarian oxidative stress in young Gclm knock-out mice suffer from ovarian failure due to an accelerated decline in ovarian follicles mediated by increased recruitment of follicles into the growing pool, followed by apoptosis at later stages of follicular development (Lim et al, 2015). We have recently shown that AOXs, vitamin C and edaravone mitigated CrVI-induced ovarian toxicity (Banu et al, 2008; Stanley et al, 2011; Stanley et al, 2013; Stanley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%